Islam Nusantara and the Challenges of Political Islam in the Contemporary World - Mahmoodreza Esfandiar (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2022)
The purpose of this study is to investigate the most important challenges of Nusantara Islam with political Islam in the contemporary world. For this purpose, first the most important Islamic intellectual currents in Indonesia, namely traditional Islam, religious reformism and liberal Islam, are discussed. The religious reform movement in Indonesia has always been influenced by major Islamic centers in the Middle East such as Mecca, Medina and Cairo. The current of traditional Islam is in fact the heritage of Islamic culture of this region. Islam liberal is also influenced by modern Muslim thinkers such as Fadl al-Rahman. This article seeks to answer these questions of how the religious reform movement in the Malay world, especially in the pre-modern Indonesian archipelago, took shape and how the traditional movement reacted to it. Also, what are the most important features of Islamic thought and the current of religious reform and intellectualism in Indonesia? Finally, a picture of the situation of these three currents in Indonesia is drawn and the important role of Islam Nusantara in resolving the crises of the contemporary period is explained with emphasis on the thoughts of Abdul Rahman wahid.